Insight from patients and healthcare professionals on the implementation of virtual clinics in patients with inflammatory bowel disease. Issue 2 (25th February 2021) - Kumar, Aditi; Quraishi, Mohammed Nabil; de Silva, Shanika; Trudgill, Nigel John; Steed, Helen; Brookes, Matthew James; Cooney, Rachel
Abstract : Introduction: During COVID-19, the management of outpatient inflammatory bowel disease (IBD) changed from face-to-face (F2F) to telephone and video consultations across the UK. We surveyed patients with IBD and IBD healthcare professionals (HCPs) to evaluate the impact of this abrupt transition on patient and HCP satisfaction outcomes, including the barriers and enablers of this service. Methods: Patient satisfaction surveys were sent to patients who had a telephone consultation from May to July 2020. A second survey was sent to IBD HCPs across the UK. Questions from both surveys consisted of a mixture of multiple-choice options, ranking answers as well as short-answer questions. Results: 210 patients and 114 HCPs completed the survey. During COVID-19, there was a significantly greater use of telephone, video or a mixture of consultation. F2F consultations were consistently preferred by patients, with 50% of patients indicating they did not want the option of for video consultations. Patients were more likely to prefer a telephone consultation if they were stable and needed routine review. Significantly fewer HCPs (5.3%) intend to use F2F consultations alone, preferring the use of telephone (20.2%) or combinations of telephone/F2F (22.8%), telephone/video (4.4%) or combination of all three consultation types (34.2%). 63% indicated they intend to incorporate video consultations in the future. Conclusion: Telephone and video consultations need to be balanced proportionately with F2F clinics to achieve both patient and HCP satisfaction. Further research needs to be done to explore the use of video medicine in patients with IBD.